ANALISIS EFISIENSI BISNIS PRODUK BUAH NANAS BEKU PADA BALI FOOD INDUSTRI - Antonius E. O Domaking; I Made Budiasa; Nyoman Yudiarini, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2024)
Bali Food Industry is a company engaged in agriculture where this company is integrated with farmers to meet fruit supply throughout the season. This company sells several processed fruit products such as frozen pineapple, frozen melon, frozen dragon, frozen red guava, frozen soursop, frozen corn, frozen strawberry and others. Pineapple is a fruit with high market demand, both for direct consumption and for processing into food products. This study aims to analyze the profitability of the frozen pineapple business in the Bali Food Industry and to analyze the efficiency of the frozen pineapple business in the Bali Food Industry. The location in this study is the Bali Food Industry which is located on Jalan Siulan Gang Sekar Sari III, Block C6, East Denpasar District, Denpasar City, Bali. This research was conducted from April 2023 to June 2023. The sample in this study was determined using the Purposive method with a total of 5 respondents, consisting of: Directors, Treasurers, Secretaries, employees in the production division, and employees in the marketing section. The results showed that the profit from the frozen pineapple fruit business in the Bali Food Industry was IDR 7,707,333.33. Analysis of the efficiency of the frozen pineapple business in the Bali Food Industry shows an R/C Ratio value of 1.57, meaning that each expenditure costs Rp. 1.00, then the frozen pineapple entrepreneur will receive Rp. 1.57. From this research, frozen pineapple business is profitable and efficient.